FEEDBACK SEEKING FOLLOWING CAREER TRANSITIONS. - Callister, R. R.; Kramer, M. W.; TURBAN, D. B. (Academy of Management Journal, 1999)
We examined how inquiring and monitoring for feedback from peers and supervisors changed over time for transferees. Hypotheses were grounded in uncertainty reduction and impression management theor...